Reconciling global and local benefits of forest restoration A shared interdisciplinary perspective - Mansourian, Stephanie; Adams, William M; Bouazza, Karma; Nunes Ferreira, Joice; Ganz, David J; Hurd, Jack; Pagiola, Stefano; Parrotta, John; Ramamonjisoa, Bruno; Ratsifandrihamanana, Nanie; Villalobos, Roger; Walters, Gretchen; et al. (University of Cambridge, 2025)
Restoring ecosystems, and forests in particular, has become a global priority. At larger scales, forest restoration must necessarily reconcile the needs and priorities of multiple stakeholders and, in doing so, raises several governance challenges. Approaching governance in the context of forest restoration through an interdisciplinary lens provides a complex picture consistent with the multiple factors that impact forest restoration. Focusing on one specific governance challenge, namely, how to balance global to local benefits of forest restoration, serves to demonstrate the complexity and value of approaching these challenges with an interdisciplinary lens. This paper presents several options, including: the need for a multi-scale and functioning governance structures or mechanisms involving decision-makers from local to national and international scales; considering multiple brokers (or “intermediaries”) as important leverage points; sharing tools with national governments that help to ensure that restoration brings a balanced flow of benefits to their citizens; redressing power imbalances by strengthening social capital and building the capacity of community-level organizations; recognizing rights (to land or forest tenure rights – whether to communities or privately to local community members); creating a dedicated funding stream for restoration; changing the focus from quantitative targets for tree planting/restoration to more multi-objective based approaches; acknowledging and emphasizing that forest restoration can yield multiple benefits for many individuals or groups, and ensuring that these can be realized.